2014
DOI: 10.1111/sum.12112
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long‐term sustainability of constructed urban soil: impact of high amounts of organic matter on soil physical properties and water transfer

Abstract: Sustainability of urban soils lies in their ability to facilitate water and air permeabilities. Exogenous organic matter has been shown to have a positive impact on these properties. Under urban conditions, a large one‐time input of an organic amendment was made to the reconstituted soil. Two organic materials, green‐waste compost (gw) or cocompost from sewage sludge and wood chips (sw), were mixed with sandy loam soil (40% v/v) and placed in 600‐L containers. Containers received a 29‐cm thick layer of sandy l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 23 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…and new porosity appeared, with elongated pores (> 550 μm radius) (Grosbellet et al, 2011). Soil water retention was also improved after 5 years (Cannavo et al, 2014). High organic matter inputs improved vegetative growth above and belowground, as described by Smith et al (2010).…”
Section: Effects Of Organic Mattermentioning
confidence: 52%
See 1 more Smart Citation
“…and new porosity appeared, with elongated pores (> 550 μm radius) (Grosbellet et al, 2011). Soil water retention was also improved after 5 years (Cannavo et al, 2014). High organic matter inputs improved vegetative growth above and belowground, as described by Smith et al (2010).…”
Section: Effects Of Organic Mattermentioning
confidence: 52%
“…In this same experiment, Cannavo et al (2014) predicted that high organic matter amendment could maintain physical properties ten years after soil reconstitution in bare soil containers. We have demonstrated here that the choice of the type of organic matter (high fertility with co-compost of sewage sludge and wood chips, medium fertility with green waste compost and low fertility with peat), used for constructed soil design, plays a determining role in the early establishment of street trees and therefore determine their longevity.…”
Section: Resultsmentioning
confidence: 95%
“…Urban soils are globally the site of major modifications (e.g., compaction, exogenous soils). For example, compaction modifies the structure of these soils (Gregory et al 2006;Cannavo et al 2014). Anthropogenic urban soils (case of unsealed soils) are most often characterized by a rapid evolutionary pattern that can be explained by an imbalance with their environment (Séré et al 2012).…”
Section: Limitation Of the Simplified Methodologymentioning
confidence: 99%
“…For example, Han et al simulated future land use scenarios of Beijing from 2010 to 2020 [43]. Cannavo et al estimated the effect of large quantities of organic matter on the soil hydrodynamic properties of reconstituted urban soil during a 10-year period by simulating the daily soil water content and water drainage in the soil profile [44]. Tian et al used the Monte Carlo stochastic method to forecast the financial sustainability of a basic pension based on predictions for the population of China, and found that the imbalance in basic pension will occur in 2026 [45].…”
Section: Introductionmentioning
confidence: 99%